Ovarian Cancer in Ghana, a 10 Year Histopathological Review of Cases at Korle Bu Teaching Hospital - Akakpo, P.K.; Derkyi-Kwarteng, L.; Gyasi, R.K.; Quayson, S.E.; Anim, J.T. (African Journal of Reproductive Health, 2015)
To determine the histopathological types, age distribution, presenting signs and symptoms of ovarian cancers diagnosed at the Korle-Bu Teaching Hospital, Ghana. All histopathology slides and request cards of ovarian cancers diagnosed over a ten-year period (2001 to 2010) were reviewed and the cancers classified according to the World Health Organization 1999 classification. Biographical and clinical data of the patients were collected and results entered into Epi-info to determine the frequency, age distribution and clinical presentation of the various types of ovarian cancer. There were 192(27.2%) ovarian cancers out of 706 ovarian tumours. Epithelial cancers were the most common: 100 (52.1%), followed by sex cord stromal cancers 66 (34.4%). Majority of epithelial cancers were serous adenocarcinomas (71/100) while most sex cord stromal cancers were adult granulosa cell tumours 46 (69.7%). The mean age of patients with adenocarcinoma was 49 years while that of the 46 adult granulosa cell tumours was 46.5years. Patients present with varying combinations of symptoms and signs and ovarian cancers present at an earlier age compared to other populations, with the age of presentation being slightly lower for sex cord stromal cancers compared to adenocarcinomas. There are no specific symptoms or signs associated with ovarian cancer at presentation, to assist with diagnosis. (Afr J Reprod Health 2015; 19[4]: 102-106).
Keywords: Ovary; Cancer; Histopathology; Demographics; Clinical features; Ghana